The effect of specific music instrumentation on anxiety reduction in university music students: A feasibility study. (July 2017) - Matney, Bill
Abstract: Researchers note the use of recorded music for anxiety reduction, but have rarely studied the effects of instrumentation. The investigator asked two questions: (a) Do string music, piano music, and marimba music each promote a reduction in anxiety, and (b) Is there a difference among these instrument types regarding their ability to facilitate anxiety reduction? Prior to giving a classroom presentation, university student participants ( N  = 54) listened to a version of Bach Air from Orchestra Suite No. 3 in D. Major, BWV 1068, using strings, piano, or marimba. Results indicated a significant difference for anxiety reduction from pretest to posttest when all participants were included as one group, or when in their separate respective groups. Analysis indicated no significant difference among the three groups for anxiety reduction. This feasibility study therefore offers preliminary indications that particular types of percussion instrumentation may be as effective as other instrumentation for anxiety reduction.